(untitled) (Kuala Lumpur, 1981)
This book introduce about rice self-sufficiency in Malaysia policy and reality. Primary commodity issues and development in Malaysia. The new international economic order and primary commodities. Industrial development strategy for Malaysia...
Keywords: Phát triển kinh tế,Economic development